The Issues in Order Picking and Packaging in a Leading Pharmaceutical Company in Malaysia - Veera Pandiyan Kaliani Sundram; Irwan Ibrahim; Mashitah Mohamed Esa; Natasya Nabilah Mohd Azly (International Journal of Supply Chain Management, 2019)
Picking and packing is the one of the main principle action in a distribution center. Picking and packing action ensures the right product at the right quantity reaches the right customer. As such, this study is purported to recognize the issues related to picking and packing error and to know how to overcome it. The study was conducted using a semi-structured interview to elicit response concerning picking and packing issues and error. Five respondents were selected to participate in the semi-organized interview and these respondents are from different designations in the picking and packing unit in a distribution center from a leading pharmaceutical company. There are several issues that relates to picking and packing error, such as multiple items/barcodes in one location, wrong carton label, and employees miscommunication. Findings from this study will explicitly provide solution for better picking and packing approaches to provide solution to picking and packing error. The novelty of this study lies on the issues of order picking and packing in a leading pharmaceutical organization in Malaysia through vigorous investigation.